Hepatic Artery Pseudoaneurysm in the Liver Transplant Recipient: A Case Series. (27th December 2019) - St. Michel, David P.; Goussous, Naeem; Orr, Nathalie L.; Barth, Rolf N.; Gray, Stephen H.; LaMattina, John C.; Bruno, David A.
Abstract : Introduction . Hepatic artery pseudoaneurysm is a rare and potentially fatal complication of liver transplantation with a reported incidence of 0.3–2.6% and associated mortality approaching 75%. Clinical presentation typically includes sudden hypotension, gastrointestinal bleed or abnormal liver function tests within two months of transplantation. We report a series of four cases of hepatic artery pseudoaneurysm in adult liver transplant recipients with the goal of identifying factors that may aid in early diagnosis, prior to the development of life threatening complications. Methods . A retrospective chart review at a high volume transplant center revealed 4 cases of hepatic artery pseudoaneurysm among 553 liver transplants (Incidence 0.72%) between March 2013 and March 2017. Results . Two of the four patients died immediately after intervention, one patient survived an additional 151 days prior to death from an unrelated condition and one patient survived at two years follow up. All cases utilized multiple imaging modalities that failed to identify the pseudoaneurysm prior to diagnosis with computed tomography angiography (CTA). Two cases had culture proven preoperative intrabdominal infections, while the remaining two cases manifested a perioperative course highly suspicious for infection (retransplant for hepatic necrosis after hepatic artery thrombosis and infected appearing vessel at reoperation, respectively). Three of the four cases either had a delayed biliary anastomosis or development of a bile leak, leading to contamination of the abdomen with bile. Additionally, three of the four cases demonstrated at least one episode of hypotension with acute anemia at least 5 days prior to diagnosis of the hepatic artery pseudoaneurysm. Conclusions . Recognition of several clinical features may increase the early identification of hepatic artery pseudoaneurysm in liver transplant recipients. These include culture proven intrabdominal infection or high clinical suspicion for infection, complicated surgical course resulting either in delayed performance of biliary anastomosis or a biliary leak, and an episode of hypotension with acute anemia. In combination, the presence of these characteristics can lead the clinician to investigate with appropriate imaging prior to the onset of life threatening complications requiring emergent intervention. This may lead to increased survival in patients with this life threatening complication.